Mechanistic insights into 125I seed implantation therapy for Cholangiocarcinoma: focus on ROS-Mediated apoptosis and the role of GPX2 - Jun Luo; Zheng Yao; Weiren Liang; Danjun Song; Hui Zeng; Yi Jiang; Zhehan Bao; Jiaping Zheng; Yinan Ding (Journal of Cancer Research and Clinical Oncology)
Abstract Objectives Cholangiocarcinoma (CCA) is a rare tumor with a poor prognosis and poses significant therapeutic challenges. Herein, we investigated the mechanism of efficacy of 125I seed implantation therapy in CCA, focusing on the induction of reactive oxygen species (ROS)-mediated apoptosis and the involvement of glutathione peroxidase 2 (GPX2). Materials and methods Human cholangiocarcinoma cell lines QBC939 and RBE were purchased for in vitro studies. In vivo studies were performed using a rabbit VX2 CCA model. Apoptosis and proliferation were detected by TUNEL staining and clone formation, respectively. ROS generation was detected by dihydroethidium staining. Histological evaluation was performed by hematoxylin and eosin staining. Protein expression was determined by Western blotting and immunohistochemistry. Results Our results demonstrate that 125I seeds effectively inhibited tumor growth in the rabbit VX2 tumor model and promoted the apoptosis of CCA cells in vitro in a dose-dependent manner. Molecular analyses indicate a marked increase in reactive oxygen species (ROS) levels following treatment with 125I seeds, suggesting the involvement of ROS-mediated apoptosis in the therapeutic mechanism. Furthermore, the downregulation of glutathione peroxidase 2 (GPX2) was observed, indicating its potential role in modulating ROS-mediated apoptosis in CCA. Conclusion 125I seed implantation therapy exerts therapeutic effects on CCA by inducing ROS-mediated apoptosis. The downregulation of GPX2 may contribute to enhanced ROS accumulation and apoptotic cell death. These findings provide mechanistic insights into the therapeutic potential of 125I seed implantation for CCA and highlight ROS-mediated apoptosis and GPX2 regulation as promising targets for further investigation and therapeutic intervention in this malignancy.